Evaluation of the Swabbing of Disposable Absorbent Incontinence Products for Assessing the Carriage of Multiresistant Enterobacteriaceae in Nursing Home Residents - Naf, Alexis; Decalonne, Marie; Santos, Sandra Dos; Mereghetti, Laurent; van der Mee-Marquet, Nathalie L. (Frontiers in Microbiology, 2017)
We compared the performance of incontinence product (IP) and rectal swabbing for the detection of multidrug-resistant Enterobacteriaceae (MDRE) carriage in a large multicenter study conducted in February 2017 among the residents of 23 French nursing homes. The study included 547 residents who habitually wore IP, 88 of whom were MDRE carriers (16.1%). Positive results were obtained for both rectal and IP swabs for 64 of these residents, for rectal swabs only for 22 and for IP swabs only for two of these patients. The estimated prevalence of MDRE carriage depended on the type of sample: 15.7% for rectal swabs and 12.1% for IP swabs (p <0.001). The positive percent agreement was 84.2% and the negative percent agreement was 97.4 %. Rectal swabbing remains the best method for detecting MDRE carriage in elderly residents, but our findings provide support for the use of swabs from IP used overnight to increase response rates in MDRE surveys in elderly residents that habitually wear IP, when rectal swabbing is not feasible.